Exogenous melatonin enhances soybean (Glycine max (L.) Merr.) seedling tolerance to saline‐alkali stress by regulating antioxidant response and DNA damage repair. Issue 4 (4th July 2022) - Zhao, Qiang; Chen, Suyu; Wang, Guangda; Du, Yanli; Zhang, Zhaoning; Yu, Gaobo; Ren, Chunyuan; Zhang, Yuxian; Du, Jidao
Abstract: Saline‐alkali (SA) stress induces excessive reactive oxygen species (ROS) accumulation in plant cells, resulting in oxidative damages of membranes, lipids, proteins, and nucleic acids. Melatonin has antioxidant protection effects in living organisms and thus has received a lot of attention. This study aimed to investigate the effect and regulating mechanism of melatonin treatment on soybean tolerance to SA stress. In this study, cultivars Heihe 49 (HH49, SA‐tolerant) and Henong 95 (HN95, SA‐sensitive) were pot‐cultured in SA soil, then treated with MT (0–300 μM) at V1 stage. SA stress induced ROS accumulation and DNA damage in the seedling roots of both cultivars, causing G1/S arrest in HN95 and G2/M arrest in HH49. Melatonin treatment enhanced the activity of antioxidant enzymes in soybean seedling roots and reduced ROS accumulation. Additionally, melatonin treatment upregulated DNA damage repair genes, thus enhancing the reduction of DNA oxidative damage under SA stress. The effects of melatonin treatment were manifested as decreased RAPD polymorphism, 8‐hydroxy‐2′‐deoxyguanine (8‐OH‐dG) level, and relative density of apurinic sites (AP‐sites). Meanwhile, melatonin treatment partially alleviated the SA‐induced G1/S arrest in HN95 and G2/M arrest in HH49, thus enhancing soybean seedling tolerance to SA stress.